Spatio-Temporal Assessment of Land Use Changes in Sonipat, Haryana: Socio Economic Impacts and Policy Intervention - Kumar, Niraj; Rana, Tejbir Singh; Anand, Subhash; Nishit (Research in Ecology, 2025)
This study examines the effects of rapid land use changes in India, with a specific focus on Sonipat District in Haryana—a region undergoing significant urban expansion. Over the past two decades, rural landscapes in Sonipat have undergone notable transformation, as open spaces and agricultural lands are increasingly converted into residential colonies, commercial hubs, and industrial zones. While such changes reflect economic development and urban growth, they also raise critical concerns about sustainability, especially in terms of food security, groundwater depletion, and environmental degradation. The study examines land use changes between 2000 and 2024 using remote sensing techniques and spatial analysis. It further incorporates secondary data and insights from community-level interactions to assess the socio-economic and ecological impacts of this transformation. The findings indicate rising land fragmentation, loss of agricultural livelihoods, pressure on civic infrastructure, and increasing pollution—factors that threaten long-term regional sustainability. The study underscores the urgent need to reconcile urban development with environmental and social sustainability. By offering a detailed case study of Sonipat, this research contributes to the broader discourse on India’s urbanisation pathways. It aims to provide policymakers, planners, and researchers with evidence-based recommendations to manage land transitions more responsibly, promoting urban growth models that ensure ecological integrity, equitable development, and long-term resilience.